Pemberdayaan Masyarakat Melalui Pengembangan Potensi Olah Raga Angkat Besi Studi: Terhadap Padepokan Gajah Lampung Tahun 2016 - Claudia Juaneta Shahnaz; Suwanto Adhi; Priyatno Harsasto (Journal of Politic and Government Studies, 2017)
ABSTRACTPoverty is one of the complex problems occurring in Indonesia. One way to overcome poverty is by empowering the community where the empowerment of these communities can be done by the government or independently by citizens or individuals who are expected to fight and reduce poverty. Community empowerment is the development process where the community took the initiative to start the process of social activities to improve the situation and conditions themselves. One of the empowerment to overcome poverty and improve people's standard of living is the empowerment done by Padepokan Gajah Lampung toward weight lifter, the basis of cooperation of this party and the Government is UU and regulations of the president. The core of UU No. 3 of 2005 and Presidential Regulation No. 16,17,18 of 2007 is that the Government has the duty and authority in the right to direct, guide, assist, and supervise the organization of sports in accordance with the laws and regulations.The research method used is qualitative approach with data collection technique that is observation, interview and document research. Informants in this research are Founder and Owner, Coaches, Athletes and former athletes of Padepokan Gajah Lampung and in this case the Government Department of Youth and Sports.The results showed that the empowerment done by Padepokan is good and has reached the goal of the empowerment itself and the Government is quite helpful but considered less maximal in terms of procurement of training facilities.Keywords : Empowerment, Partnership, Athlete